The advertisement calls of two species of Brachycephalus (Anura: Brachycephalidae) from southern Atlantic Forest, Brazil - Monteiro, Juliane Petry De Carli; Condez, Thais Helena; Garcia, Paulo Christiano De Anchietta; Haddad, Célio Fernando Baptista (Zootaxa, 2018)
The advertisement calls are known for only eight species within the genus Brachycephalus. Herein, we describe the advertisement calls of B. olivaceus and B. quiririensis, both species from southern Atlantic Forest, state of Santa Catarina, Brazil. The advertisement calls of these species are similar, composed by one short and high-frequency note. The parameters range overlap between calls, as exemplified by the dominant frequency of 6.4–7.0 kHz in B. olivaceus and 6.2–6.5 kHz in B. quiririensis. Additionally, we provide a compilation of the available bioacoustic information for this genus.